On Not Knowing. - Beauregard, Guy (Canadian Literature)
The article presents author's views on political aspects related to life of people in Japan after the earthquake on March 11, 2011. Topics discussed include demolished building of Fukushima Daiichi Nuclear Power Station, transpacific dimensions of Asian Canadian relations, social production of valuable culture.